Analisis Strategi Pemasaran Jamur Tiram (Pleurotus Ostreatus) Studi Kasus: Pt. Mushiro Jaya Group Medan - Muhammad Muklis Fauzan; Khairunnisa Rangkuti; Hardiansyah Sinaga (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
The agricultural sector, especially horticulture, is crucial for Indonesia's economy. PT. Mushiro Jaya Group, an oyster mushroom farm, saw rising sales but faced marketing and competition challenges. This study aimed to analyze its internal and external factors and formulate priority marketing strategies. Using a descriptive qualitative method and purposive sampling, data were analyzed with IFE, EFE, SWOT, and QSPM matrices. Results showed a strong internal position (IFE: 3.10) and a responsive external position (EFE: 2.89), placing the company in a growth quadrant. QSPM analysis selected three top-priority strategies: (1) building partnerships with traders and culinary businesses (TAS 6.010), (2) diversifying products and packaging sizes (TAS 5.253), and (3) improving production efficiency via staff training and facility upgrades (TAS 5.242). These strategies are designed to optimize strengths and opportunities to enhance competitiveness and ensure sustainable growth.